TASK-ORIENTED TEMPERATURE COMPENSATION AS AN INSTRUMENT FOR REDUCTION OF UNCERTAINTY IN SHOP FLOOR CMM (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The significance of Shop Floor CMM in inspecting mechanical parts in modern industries, such as automotive and aerospace, has been increasing in recent years, making it an integral part of the inspection process. However, a major issue that remains is the uncertainty, particularly caused by changes in environmental conditions, such as ambient temperature, in shop floor conditions. Task-oriented temperature compensation software can solve these problems. Its effectiveness can be evaluated through uncertainty analysis.